Enhancing young learners' interest in English through play-based learning in EFL contexts - Wahyu Nanda Sari; Dominique Savio Nsengiyumva; Didik Rinan Sumekto (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2026)
This study aims to examine how play-based learning influences young children's interest in learning English in an English as a Foreign Language (EFL) context. A descriptive qualitative research design was employed involving first- to third-grade elementary school students enrolled in an English tutoring program. Data were collected through classroom video recordings of play-based English learning activities and analyzed thematically using four indicators of learning interest: focused attention, enthusiasm, active participation, and persistence. The findings revealed that play-based learning created a positive and enjoyable learning environment that enhanced students' interest in learning English. The analyzed classroom interactions showed that learners maintained greater attention, demonstrated higher enthusiasm, participated more actively in learning activities, and exhibited stronger persistence when completing English tasks through games and other interactive activities. These findings suggest that play-based learning is an effective instructional approach for fostering young learners' interest in English learning in EFL contexts. This study contributes to the growing body of knowledge on early childhood English language education by emphasizing the importance of integrating age-appropriate, child-centered, and interactive learning activities into English instruction to promote meaningful engagement and support effective language learning among young children.